CLINIC EFFICIENCY OF MYOCARDIAL REVASCULARIZATION FOR CARDIAC ALLOGRAFT VASCULOPATHY - B. L. Mironkov; V. V. Chestukhin; I. Yu. Tyunyaeva; I. G. Ryadovoy; E. N. Ostroumov; A. O. Shevchenko; A. B. Mironkov; A. Ya. Kormer (Вестник трансплантологии и искусственных органов)
Aim of the study is to show the pathogenetic importance of myocardial revascularization and to estimate quantitatively effi ciency of the treatment of cardiac allograft vasculopathy after heart transplantation.Materials and methods. 30 percutaneous coronary interventions (PCI) were performed to recipients of heart transplant (8 men and 7 women, aged from 18 to 56 years), who were diagnosed with cardiac allograft vasculopathy by coronary angiography within the time period from 1,5 to 12 years after heart transplantation. Before revascularization and one week after tolerances to physical activity, volume characteristics of the left ventricle were defi ned and diastolic function of heart was estimated. Average term of observation after stenting was 35,5 ± 5,5 months.Results. Tolerance to physical activity (from 76,6 ± 8,5 to 116,9 ± 9,6 W), its duration (from 5,4 ± 2,2 to 8,5 ± 4,1 min) and rate pressure product – RPP (from 198 ± 15 to 247 ± 24 P < 0,05) increased. There was a restoration of diastolic function (Ve/Va from 0,57 ± 0,18 to 1,15 ± 0,2 P < 0,05). Signifi cant distinction in time frames of vasculopathy development, frequency and reasons of repeated interventions depending on age of patients is revealed. In the group of patients younger than 30 years of age (7 patients), the time interval between heart transplantation and vasculopathy development is twice shorter, than in more senior patient group, over 45 years old (8 patients). Young patients showed the expressed tendency to develop stent restenosis (20 coronary interventions).Conclusion. Dynamics in functional condition of the left ventricle as a result of revascularization confi rms the leading role of miocardial ischemia in pathogenesis of transplant insuffi ciency due to vasculopathy. The signifi cant factor infl uencing upon long-term result of coronary intervention is the age of the patient.